Penerapan Metode Tutor Sebaya Untuk Meningkatkan Hafalan Q.S. Yunus Ayat 40-41 Dan Q.S. Al-Ma’idah Ayat 32 Pada Pembelajaran Al-Qur’an Dan Hadits - Komariah, Oom; Hidayati , Nurul; Nurmilah , Nurmilah (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aimed to investigate the impact of social media use in MIS An Nazah’ academic achievement. This study used a quantitative research method with a correlational research design. The sample of this study consisted of 100 high school students selected randomly. The research instrument was a questionnaire. The results showed a positive correlation between the frequency of using social media for learning and students’ academic achievement. However, the correlation between the duration of using social media for non-learning purposes and students’ academic achievement showed negative results. The conclusion of this study is that the use of social media can be an effective tool to improve students’ academic achievement if used appropriately and wisely.